(untitled) (Eurasian Journal of Ecology, 2018)
The article presents the screening of parent variety of spring wheat Erithrospermum-35 and M7 mutant lines developed on its genetic basis using gamma radiation dose of 200 Gy on the elements of productivity and grain protein content in plants grown under irrigation and drought. New sources of mutant germplasm were identified for genetic improvement of quantitative traits of productivity, as the thousand grains weight and grain weight per spike and grain protein content. The wheat mutant germplasm, grown under irrigation had 12 samples, which are characterized by significantly increase in thousand grains weight. Under drought conditions thousand grains weight decreased by 2,1-2,3 times, to a lesser extent compared as the Erithrospermum-35. The genetic variability of the grains weight per spike shows significantly higher thousand grains weight, indicating its greater potential for improving drought resistance. A high correlation was found between the GPC and the elements of productivity of mutant germplasm. At the same time, this relationship is more pronounced for grains weight per spike. Key words: grain protein content, M7 mutant lines of Eritrospermum-35 varieties of spring wheat, relationship between grain protein content and thousand grains weight and grains weightper spike.